(untitled) (Encuentros, 2023)
This paper presents a state of art, based on a documentary review of research in master’s and doctoral theses, on the concept of necropolitics in Ibero-America between the years 2017-2021. The objectives that guided its realization were the following: 1) to identify the relevant trends of the studies in necropolitics, 2) to describe the new concepts that demonstrate their polysemy, and 3) to discuss the ruptures and continuities from biopolitics. This review allows to conclude that the study of necropower is dynamic and works as a theory and category of analysis in the study of the different forms of violence and death, according to contemporary social sciences.